THE EFFEECTS OF TREBON ON Cyprinus carpio L. LARVAE AND DETERMINATION OF ITS RESIDUES - AL – Mashhadani, Hussain; Kaddou, Ibrahhim (Iraqi Journal of Science, 2024)
Toxic effects of trebon were investigated together with behavioral changes of common carp larvae, Cyprinus carpio L. exposed to the insecticide..The LC50 of Trebon to fish larvae exposed to insecticide during a period of 96 hour was 0.184 mg/L, for fish weights from 4 gms to 6 gms.Results indicated that rate of toxicity of Trebon residues to the fish was 0.323 mg/g of fish which was taken from the highest concentration that kill 100% (0.45 mg/L) which was analysed by the U.V- visible spectrophotometer.